Physical properties of palm ash mixed with phenolic resin - Mohd Radzi, Ali; Shamsul Baharin, Jamaludin, Prof. Dr.; Nur Hidayah, A. Z.; CheMohd Ruzaidi (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.